1991
DOI: 10.1007/bf02285457
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of iodine 131 metaiodobenzylguanidine for treatment of resistant neuroblastoma: results of a UK study

Abstract: In 1987, the United Kingdom Children's Cancer Study Group (UKCCSG) set up a multi-centre study to investigate the toxicity of iodine 131 metaiodobenzylguanidine (mIBG) in the treatment of resistant neuroblastoma. Since December 1987, 25 children suffering from neuroblastoma have been treated with 131I-mIBG at six UK centres. All centres followed standardised physics and clinical protocols to provide consistent toxicity and dosimetry data. These protocols describe the methods employed for both the tracer study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
2
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 7 publications
4
31
2
3
Order By: Relevance
“…Another application of the AHASA approach is in 131 ImIBG therapy of paediatric neuroblastoma, where the absorbed dose limit for acute myelodepression of 2 Gy (MTAD) to the red marrow was established by Fielding et al in 1991 [10]. The VERITAS multicentre controlled trial is currently in development.…”
Section: Formalization Of the Optimization Principle In The New Europmentioning
confidence: 99%
“…Another application of the AHASA approach is in 131 ImIBG therapy of paediatric neuroblastoma, where the absorbed dose limit for acute myelodepression of 2 Gy (MTAD) to the red marrow was established by Fielding et al in 1991 [10]. The VERITAS multicentre controlled trial is currently in development.…”
Section: Formalization Of the Optimization Principle In The New Europmentioning
confidence: 99%
“…However, European regulations now stipulate the need to perform individual patient treatment planning for TRT (4). To date, there have been few studies whereby the feasibility or potential benefit of dosimetry-based treatment planning has been examined (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Treating human neuroblastoma-bearing mice with 131 I-labeled antibody, Cheung et al (1986) showed that at least 42 Gy was required for permanent cure. The absorbed radiation dose in human neuroblastoma patients was 20 Gy on average but appeared to be highly variable, ranging from 2 to 63 without a clear correlation with tumor response (Matthay et al, 1991;Fielding et al, 1991;Wafelman et al, 1994). Accordingly, the average [ 131 I]MIBG tumor uptake should be increased 2 to 3 times over currently achieved levels, to attain exposures with theoretically curative potential (Fowler, 1990;Knox et al, 1992;Humm, 1996).…”
mentioning
confidence: 99%